Predicting the potential ecological niche distribution of Slovenian forests under climate change using MaxEnt modelling - Gregorčič, Tim; Rozman, Andrej; Repe, Blaž (Acta geographica Slovenica, 2023)
The aim of the article is to assess the potential impacts of climate change on Slovenian forests in the period 2080–2100 based on two climate scenarios: SSP1-2.6 (optimistic) and SSP5-8.5 (pessimistic) using the MaxEnt software. Slovenian forests are divided at the ecological community level into thirteen forest vegetation types. Analyses of changes in ecological niche areas, distances of vectors between centroids of present areas and future ecological niches, and general spatial changes are carried out. In addition, changes in the altitudinal zones of forest vegetation types were investigated. The results indicate significant changes for Thermophilous beech forests and Thermophilous hop-hornbeam, sessile oak, downy oak, Scots pine and black pine forests. The potential changes in the altitudinal zones of forest vegetation types indicate a clear trend of forest vegetation types moving to higher altitudinal zones.